The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0003122410380868
|View full text |Cite
|
Sign up to set email alerts
|

Racial Segregation and the American Foreclosure Crisis

Abstract: Although the rise in subprime lending and the ensuing wave of foreclosures was partly a result of market forces that have been well-identified in the literature, in the United States it was also a highly racialized process. We argue that residential segregation created a unique niche of poor minority clients who were differentially marketed risky subprime loans that were in great demand for use in mortgage-backed securities that could be sold on secondary markets. We test this argument by regressing foreclosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
398
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(409 citation statements)
references
References 69 publications
10
398
1
Order By: Relevance
“…Regardless of the level of uncertainty in the economic environment, the black group is segregated across the occupational spectrum. This is consistent with Rugh and Massey (2010) mentioned in the previous section, but also with Lacy (2012) who looked at the foreclosure rates of the black group by level of income. The findings show that the foreclosure rate of borrowers from the black group is the highest amongst low-income, but remains at the same level, around 10 percent, also for high-income borrowers.…”
Section: Cumulative Identities In the Us: Class Race And Gender Strsupporting
confidence: 91%
See 1 more Smart Citation
“…Regardless of the level of uncertainty in the economic environment, the black group is segregated across the occupational spectrum. This is consistent with Rugh and Massey (2010) mentioned in the previous section, but also with Lacy (2012) who looked at the foreclosure rates of the black group by level of income. The findings show that the foreclosure rate of borrowers from the black group is the highest amongst low-income, but remains at the same level, around 10 percent, also for high-income borrowers.…”
Section: Cumulative Identities In the Us: Class Race And Gender Strsupporting
confidence: 91%
“…The last thirty years have indeed been characterised by the evolution of financial exclusion of poor and minority households into their financial exploitation. Rugh and Massey (2010) estimate the effect of residential racial segregation on foreclosures in the US, controlling for factors such as housing price inflation, overbuilding, excessive subprime lending, and failure to assess creditworthiness. The results…”
Section: From Growth To Crisis: Capital Accumulation and Inequalitymentioning
confidence: 99%
“…Within this context, it is possible to observe links between the spatial concentration of foreclosures and falling property values at the neighborhood level [22][23][24][25][26]. Relationships have also been observed with increases in crime rates [27][28][29][30][31] and racial segregation [32,33]. Several studies have also focused on the negative effects that increases in the number of foreclosures have had on public health [34][35][36][37] and on how different groups of local residents perceive the quality of life in their respective neighborhoods [38].…”
Section: Introductionmentioning
confidence: 99%
“…If such neighborhoods are indeed more vulnerable to foreclosures, this would imply that the main effects of racial/ethnic heterogeneity and racial segregation, as well as their interaction, will have positive effects, as noted in Table 1. Whereas one study showed that metropolitan areas with more racial segregation experienced higher foreclosure rates (Rugh and Massey 2010), we test whether the combination of foreclosures and segregation also translates into higher crime rates.…”
Section: Social Distance As a Moderator Of The Foreclosures And Crimementioning
confidence: 93%